Up-Down Chair: A novel mechatronic device to assess otolith function in patients with vestibular disorders. Issue 3 (March 2016) - Bassi Luciani, Lorenzo; Martelli, Dario; Monaco, Vito; Genovese, Vincenzo; Micera, Silvestro
Highlights: A novel mechatronic platform aimed at investigating otolith function is proposed. The device is able to provide a wide range of controllable vertical oscillations. Dynamic Visual Acuity was measured during different perturbation intensities. Results revealed a good agreement between expected and measured kinematic patterns. The proposed paradigm was effective in inducing oscillopsia in enrolled subjects. Abstract: This paper describes a novel mechatronic platform, named "Up-Down Chair" (UDC), aimed at investigating otolith function in patients with vestibular disorders. The UDC was designed to provide a wide range of repeatable and controllable vertical oscillations of the head whose kinematic features match those encountered during daily activities. The following parameters were assessed to characterize the performance of the UDC: accordance between expected and measured kinematics in both loaded and unloaded conditions; Dynamic Visual Acuity (DVA) of a group of 15 healthy subjects who were asked to identify a set of Snellen optotypes while being repeatedly moved at different perturbation intensities. Results revealed a good agreement between expected and measured kinematic patterns, and excellent reliability of DVA assessed across enrolled participants. In addition, we observed that the proposed paradigm was effective in inducing oscillopsia in enrolled subjects and that the frequency of the oscillation significantly induced blurred vision during the experimental tests. The UDC appears to be usable as a complementary vestibular clinical test to investigate the effects of therapeutic treatments while applying a wide range of physiological stimuli compatible with those encountered during daily activities.